Management Practices Associated With Prevalence of Lameness in Lambs in 2012–2013 in 1,271 English Sheep Flocks - Lewis, Katharine Eleanor; Green, Laura Elizabeth (Frontiers in Veterinary Science, 2020)
The evidence base for management practices associated with low prevalence of lameness in ewes is robust. Current best practice is prompt treatment of even mildly lame sheep with parenteral and topical antibiotics with no routine or therapeutic foot trimming and avoiding routine footbathing. To date, comparatively little is known about management of lameness in lambs. Data came from a questionnaire completed by 1,271 English sheep farmers in 2013. Latent class (LC) analyses were used to investigate associations between treatment of footrot and geometric mean flock prevalence of lameness (GMPL) in lambs and ewes, with multinomial models used to investigate effects of flock management with treatment. Different flock typologies were identified for ewes and lambs. In both ewe and lamb models, there was an LC (1) with GMPL <2%, where infectious causes of lameness were rare, and farmers rarely treated lame animals. There was a second LC in ewes only (GMPL 3.2%) where infectious causes of lameness were present but farmers followed “best practice” and apparently controlled lameness. In other typologies, farmers did not use best practice and had higher GMPL than LC1 (3.9–4.2% and 2.8–3.5%, respectively). In the multinomial model, farmers were more likely to use parenteral antibiotics to treat lambs when more than 2–5% of lambs were lame compared with ≤2%. Once >10% of lambs were lame, while farmers were likely to use parenteral antibiotics, only sheep with locomotion score >2 were considered lame, leaving lame sheep untreated, potentially allowing spread of footrot. These farmers also used poor practices of routine foot trimming and footbathing, delayed culling, and poor biosecurity. We conclude there are no managements beneficial to manage lameness in lambs different from those for ewes; however, currently lameness in lambs is not treated using “best practice.” In flocks with <2% prevalence of all lameness, where infectious causes of lameness were rare, farmers rarely treated lame animals but also did not practice poor managements of routine foot trimming or footbathing. If more farmers adopted “best practice” in ewes and lambs, the prevalence of lameness in lambs could be reduced to <2%, antibiotic use would be reduced, and sheep welfare would be improved.